2017
DOI: 10.1111/raq.12190
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture of two commercially important molluscs (abalone and limpet): existing knowledge and future prospects

Abstract: Molluscan aquaculture produces the most food fish by volume in the global mariculture market. The historical, cultural and ecological value of molluscs makes them a highly sought‐after delicacy in many regions of the world. Specifically, the aquaculture of abalone and that of limpets are two key industries with striking similarities and importance within the context of food production and food security. In this review, the current knowledge of these two commercially important seafood species is explored for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Introduction of mollusc species on a commercial production level is largely determined by its seed production. While the spawning of abalone has become routine and breeding and rearing protocols are well established (Mau & Jha, ), allowing an overall production from aquaculture of 140,614 tons (FAO, ) compared to only 7,227 tons from harvesting (FAO, ) in 2015, the sustainable aquaculture of limpets still requires successful spawning and larval rearing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of mollusc species on a commercial production level is largely determined by its seed production. While the spawning of abalone has become routine and breeding and rearing protocols are well established (Mau & Jha, ), allowing an overall production from aquaculture of 140,614 tons (FAO, ) compared to only 7,227 tons from harvesting (FAO, ) in 2015, the sustainable aquaculture of limpets still requires successful spawning and larval rearing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It is surmised that any new methodologies which could save such individuals and guarantee their long-term survival would be welcomed. Such methodologies would also be applicable to develop conservation strategies for other limpet species and the emerging field of lim pet aquaculture (Angel et al 2006, Mau & Jha 2017.…”
Section: Harbours and Re-introduction In Natural Habitats: An Unsolvementioning
confidence: 99%
“…Therefore, there is debate with regards to limpet larval development (lecitotrophy versus planktotrophy). Whereas Smith () unsuccessfully used microalgae for feeding the veliger stage in larval cultures of true limpets, others have routinely added them in their protocols (De Azevedo, ; Mau & Jha, ). On the other hand, Hadfield, Strathmann, and Strathmann () suggested that for most of the basal gastropod clades, all surviving species may lack feeding larval stages, despite many of them having planktonic veliger larvae, and have provided evidence of this for several species.…”
Section: Discussionmentioning
confidence: 99%